2012
DOI: 10.1155/2012/652693
|View full text |Cite
|
Sign up to set email alerts
|

Local People Attitudes towards Community Forestry Practices: A Case Study of Kosti Province-Central Sudan

Abstract: This paper examines the attitudes of local communities toward community forestry programmes implemented by a project under the CF approach in Kosti area, based on a survey of 100 people living there. The household was the basic unit of data collection; ten villages were selected as study localities. Ten respondents from each village were randomly chosen for the interview. Frequency distribution results showed that almost all the respondents have a particularly favourable perception of the community forestry pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…This knowledge was reflected by the number of uses they were able to mention and it was a manifestation that trees formed an integral part of their daily life. Similar experience was reported by Kobbail (2012) , a farmer is primarily interested in using forests for commercial use, to improve their economic well-being rather than other benefits like for the provision of environmental services (e.g. climate regulation, erosion control and biodiversity conservation).…”
Section: Values Of Forest Resourcessupporting
confidence: 52%
“…This knowledge was reflected by the number of uses they were able to mention and it was a manifestation that trees formed an integral part of their daily life. Similar experience was reported by Kobbail (2012) , a farmer is primarily interested in using forests for commercial use, to improve their economic well-being rather than other benefits like for the provision of environmental services (e.g. climate regulation, erosion control and biodiversity conservation).…”
Section: Values Of Forest Resourcessupporting
confidence: 52%
“…CFGs build upon established systems of authority in villages and attendance at meetings does not automatically guarantee that women or people from low socio-economic groups will actively participate because they fear that their opinions will not be respected (Agarwal, 2001;Sunam and McCarthy, 2010;Kobbail, 2012). Access to CFG-managed forest resources is often not equitable but the CFGs are often stable because poor people have no choice and the hope to gain in the long run (Chakraborty, 2001; also see Persha and Andersson, 2014).…”
Section: Socio-economic Status and Gender Based Inequalitymentioning
confidence: 99%
“…However, CFGs which build on existing power structures (usually male village leaders) are more stable and poor people often retain membership because they hope to gain in the long term (Chakraborty, 2001). Similarly, economic circumstances may push women to participate out of necessity (Agarwal, 2010) but land management practices may likely become less sustainable through opportunistic overharvesting (see Hébert and Rosen (2007) in Mexico; Agarwal (2001) and Persha and Andersson (2014) in Nepal; Kobbail (2012) in Sudan).…”
Section: Secure Property (Tree and Land) Rightsmentioning
confidence: 99%
“…Therefore, the benefits that local communities derive from the BLSCRP are more likely to induce positive attitude towards the project. For example, in Kosti Province of White Nile area of Central Sudan, Kobbail (2012) found that local communities developed a positive attitude towards a reforestation project that addressed their socio-economic needs (e.g. employment creation, and food and medicinal plants privision).…”
Section: Discussionmentioning
confidence: 99%